The influence of sensation of orientation on urban park visitation - Tahroodi, Faezeh Mohammadi; Ujang, Norsidah (Universiti Putra Malaysia Press, 2020)
A sensation of orientation is a sense that provides way-finding ability and seamless experience of urban spaces including public parks. This paper examines the relationship between the sensation of orientation attributes and urban park visitation pattern. The sampling areas of the study are the Taman Tasik Titiwangsa (TTT) and the Perdana Botanical Garden (PBG), located in the city center of Kuala Lumpur, Malaysia. The study applied photo questionnaires survey involving 330 park users to determine the extent of place engagement in Activity Nodes (ANs), familiarity with legible elements, and the purpose of visiting the parks. Statistical-graphical analysis verifies that social activity is the primary purpose of visiting the parks, which is highly related to the extent of familiarity with Activity Nodes (ANs) and place engagement. The findings inform the importance of legible elements and social activities in designing urban parks to increase place attraction and to encourage park visitation.